Contamination of healthcare workers' mobile phones by epidemic viruses. (May 2016) - Pillet, S.; Berthelot, P.; Gagneux-Brunon, A.; Mory, O.; Gay, C.; Viallon, A.; Lucht, F.; Pozzetto, B.; Botelho-Nevers, E.
Abstract: Mobile phones (MPs) are potential reservoirs of nosocomial bacteria, but few data are available concerning viruses. We aimed to evaluate the presence of virus RNA from epidemic viruses including metapneumovirus, respiratory syncytial virus, influenza viruses, rotavirus (RV) and norovirus on the MPs used by healthcare workers (HCWs) and to relate it to hygiene measures. An anonymous behavioural questionnaire about MP use at hospital was administered to the HCWs of four adult and paediatric departments of a university hospital. After sampling personal (PMP) and/or professional MPs (digital enhanced cordless telephone, DECT), virus RNAs were extracted and amplified by one-step real-time reverse transcription–quantitative PCR. The molecular results were analysed in a masked manner in relation to the behavioural survey. Questionnaires from 114 HCWs (35 senior physicians, 30 residents, 32 nurses, 27 nurses' assistants) working either in adult ( n  = 58) or paediatric ( n  = 56) departments were analysed. Medical personnel used their PMP more frequently than paramedical HCWs (33/65 vs. 10/59, p <0.001). MPs were used during care more frequently in adult wards than in paediatric ones (46/58 vs. 27/56, p <0.001). Virus RNA was detected on 42/109 (38.5%) collected MPs, with RV found on 39, respiratory syncytial virus on three and metapneumovirus on one. The presence of virus RNA was significantly associated with MPs from the paediatric HCWs (p <0.001). MPs routinely used in hospital, even during care, can host virus RNA, especially RV. Promotion of frequent hand hygiene before and after MP use, along with frequent cleaning of MPs, should be encouraged.